IgG4-related pleuritis diagnosed by local anesthesia thoracoscopy; a case report and literature review - Genki Inui; Tomoya Harada; Karen Makishima; Aditya Sri Listyoko; Shunsuke Ohga; Miyu Nishigami; Hiroyuki Tanaka; Hiroki Ishikawa; Hiroki Kohno; Yoshihiro Funaki; Miki Takata; Ryota Okazaki; et al. (Respiratory Medicine Case Reports)
IgG4-related pleuritis is rare in patients with IgG4-related diseases (IgG4RD). We report a case of IgG4-related pleuritis diagnosed in a 77-year-old Japanese man with right pleural effusion. The pleural effusion exhibited lymphocyte-predominant exudates with elevated adenosine deaminase (ADA) and IgG4 levels, along with the presence of plasma cells. A pleural biopsy via local anesthesia thoracoscopy (LAT) confirmed the diagnosis of IgG4-related pleuritis, and the patient was treated with prednisolone and azathioprine. Although ADA is a well-known useful marker for diagnosing tuberculous pleuritis, a review of 14 reported cases of IgG4-related pleuritis demonstrated a positive correlation between IgG4 and ADA in pleural effusion (ρ = 0.705, p < 0.05), suggesting that ADA levels could be elevated in IgG4-related pleuritis. Furthermore, all cases with available cytology reports showed the presence of plasma cells, indicating that detecting plasma cells could aid in diagnosis. Pleural biopsy remains the gold standard for the diagnosis of IgG4-related pleuritis. LAT is a safe and effective diagnostic procedure for older patients, enabling direct visualization and biopsy of pleural lesions without intubation. IgG4-related pleuritis presents with specific findings, including dense white granulomatous lesions, vesicular nodular changes, nonspecific inflammatory changes, and pleural thickening. IgG4-positive plasma cells can be detected even in biopsies with diffuse, nonspecific findings. Therefore, LAT is a valuable and safe tool for diagnosing IgG4-related pleuritis. In conclusion, exudative pleural effusion with elevated ADA levels should prompt the consideration of IgG4-related pleuritis in the differential diagnosis. LAT is a minimally invasive and highly accurate diagnostic tool for IgG4-related pleuritis.